Russian Federation Capital Markets : Analysis and Diagnosis of the Financial Regulatory and Institutional Policies Required for Becoming an International Financial Center - Pollner, John D. (World Bank, Washington, DC, 2013)
There should be two principal goals in developing Russia as a financial center: a) attracting more of the financial business of large enterprises and of the wealthy, which now largely goes abroad to other international financial centers; and b) serving the needs of small and medium enterprises and small investors in Russia, needs that are now largely unmet. Advancing the second goal would help to advance the first goal by broadening the diversity in securities market funding as well as firm issuance possibilities. Financial centers exhibit benefits of scale. Better serving the need of Small and Medium Enterprise (SMEs) and small investors would increase both the supply of securities and the demand for securities in Moscow. An increased volume and liquidity of transactions will make Moscow a more competitive financial center, thereby attracting more of the business of large enterprises and the wealthy that currently goes elsewhere. Finally, the above actions will constitute the necessary conditions to have the key elements for developing a significant financial center. They may not be all sufficient measures however. Non-financial market factors such as a suitable macroeconomic environment, efficient city transport facilities, reasonable housing availability, education facilities for foreigners, and a streamlined and transparent business regulatory environment all constitute key ancillary aspects supporting the growth and broader operating environment of international financial centers.